THE RELATIONSHIP BETWEEN MOSQUE CHARACTERISTICS, ACTIVITIES, AND PERCEPTIONS OF SPIRITUAL VALUES - Ratu Sonya Mentari Haerdy; Hanson Endra Kusuma (Journal of Islamic Architecture, 2022)
A mosque is one of the art products formed by the spiritual values of Islamic religion. At this time, mosques are not always related to religious activities. Therefore, Everyone can visit mosques. The mosque is used as a place of worship and social-cultural interaction. This study aims to reveal the relationship between the characteristics of the mosque, the activities, and the user's perception of spiritual values. In this study, respondent data was collected by distributing online questionnaires with the results of 198 respondents. The data is then analyzed by quantitative methods through factor analysis to determine latent variables. Furthermore, a multivariate correlation analysis between latent variables was conducted to find the relationship between variables. The findings revealed the highest and most significant correlation between the characteristics of the mosque and ritual worship activities on the perception of solemnity during worship. Meanwhile, the mosque features also highly correlate with recreational activities, giving rise to the perception of openness to the mosque building.